2017
DOI: 10.1038/cdd.2017.54
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin ligase LIN41/TRIM71 targets p53 to antagonize cell death and differentiation pathways during stem cell differentiation

Abstract: Rapidity and specificity are characteristic features of proteolysis mediated by the ubiquitin-proteasome system. Therefore, the UPS is ideally suited for the remodeling of the embryonic stem cell proteome during the transition from pluripotent to differentiated states and its inverse, the generation of inducible pluripotent stem cells. The Trim-NHL family member LIN41 is among the first E3 ubiquitin ligases to be linked to stem cell pluripotency and reprogramming. Initially discovered in C. elegans as a downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 52 publications
4
55
0
1
Order By: Relevance
“…Lastly, TRIM71 (also known as LIN41) has been demonstrated to regulate p53 during stem cell differentiation [117]. TRIM71 KO mice are embryonically lethal due to the failure of the neural tube to close during development [114,115].…”
Section: Trim Proteins (Trim24 Trim28 Trim29 Trim39 Trim69 and Tmentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, TRIM71 (also known as LIN41) has been demonstrated to regulate p53 during stem cell differentiation [117]. TRIM71 KO mice are embryonically lethal due to the failure of the neural tube to close during development [114,115].…”
Section: Trim Proteins (Trim24 Trim28 Trim29 Trim39 Trim69 and Tmentioning
confidence: 99%
“…TRIM71 KO mice are embryonically lethal due to the failure of the neural tube to close during development [114,115]. A recent study has demonstrated that TRIM71-mediated regulation of p53 is likely critical in facilitating normal embryonic stem cell differentiation and neurogenesis [117]. TRIM71 has been shown to bind p53 through its NHL domain, and is able to ubiquitinate p53 in embryonic stem cells [117].…”
Section: Trim Proteins (Trim24 Trim28 Trim29 Trim39 Trim69 and Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Intriguingly, through our recent work by screening mutant p53-interacting proteins in ovarian cancer as previously 9 described (Chen et al, 2019), we unexpectedly found that mutant p53 may interact with a peptide (KLQDQALKE) encoded by the SEPT4 gene through a co-immunoprecipitation (co-IP) assay coupled with mass spectrometry (MS) analysis ( Figure 4A). This observation prompted us to test if ARTS binds to wild-type p53 as well, because both wild-type and mutant p53 share common binding partners in many cases, such as MDM2 and TRIM71 (Nguyen et al, 2017, Chen et al, 2019. By co-expressing exogenous p53 and Flag-ARTS in H1299 cells followed by co-IP-IB assays, we found that exogenous p53 could be co-immunoprecipitated with Flag-ARTS using an anti-Flag antibody ( Figure 4B).…”
Section: Arts Expression Is Induced By P53 In Cancer Cellsmentioning
confidence: 99%